Martha Nussbaum: Disgust as a Political Emotion (Itinera, 2017)
Martha Nussbaum considers disgust a "political emotion" that is at the base of both negative value judgments and intolerance towards diversity. The purpose of this paper is to show the relation between Nussbaum's analysis of disgust and her ethical-political theory. In particular, the paper aims at highlighting some essential elements of this theory: the role of the body in social dynamics, the reformulation of the concepts of human nature and dignity, the relation between perception and evaluation, the public role of imagination and art, the importance of moral psychology.Â